Optimization of Production Capacity Jumbo Bag by Method Theory of Constraints - Brilian, Delinda; Rochmoeljati, Rr. (Journal La Multiapp, 2025)
PT. XYZ is a company engaged in production jumbo bag with a capacity of 500–2000 kg. Increased demand occurred in jumbo bag with a capacity of 500 kg which causes problems in the production process, especially at work stations Cutting (SK-4), which experienced obstacles in the form of bottleneck due to limited resource capacity. This condition hampers efficiency and productivity, so that companies are unable to meet production targets during the period May to October 2024. This research aims to optimize production capacity jumbo bag by applying Theory of Constraints (TOC) through approach Drum-Buffer-Rope And Linear Programming which is processed using software POM-QM. Research stages include identification constraint, exploitation constraint, non-subordinatin constraint, as well as elevation constraint. From the results of this research, a solution was obtained in the form of addition shift work at the station Cutting (SK-4) through reduction shift at the station Needle Loom (SK-3) without reducing the number of operators, managed to increase the efficiency of the production process significantly. The implementation results show an increase in production time capacity from 129511 minutes to 291399.8 minutes (an increase of 26%) as well as an increase output production of 1,476 unit to 3,320 unit. Thus, the company managed to overcome obstacles bottleneck, increase operational productivity, and achieve predetermined production targets more optimally.